2020
DOI: 10.7759/cureus.8171
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Cerebral Vasospasm After Transsphenoidal Tumor Resection: Two Case Reports and Systematic Literature Review

Abstract: Budnick et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Budnick et al reviewed the 34 cases of all-cause post-TSS vasospasm, including pituitary adenoma. They reported that SAH proceeded with the onset of symptomatic vasospasm in a large proportion (70.6%) of their patients [23]. Even though our patient did not suffer complications following surgery, including SAH or CSF leakage, our literature review found that 85.2% of those pituitary adenoma patients who experienced vasospasm post-TSS had SAH.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Budnick et al reviewed the 34 cases of all-cause post-TSS vasospasm, including pituitary adenoma. They reported that SAH proceeded with the onset of symptomatic vasospasm in a large proportion (70.6%) of their patients [23]. Even though our patient did not suffer complications following surgery, including SAH or CSF leakage, our literature review found that 85.2% of those pituitary adenoma patients who experienced vasospasm post-TSS had SAH.…”
Section: Discussionmentioning
confidence: 51%
“…Besides our patients, we also identified 27 cases of pituitary adenoma and 17 publications [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] related to this condi- tion. To the best of our knowledge, this is the first patient under 18 years old in our literature review who also has undergone a thrombectomy in her admission after uncomplicated TSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral vasospasm (CVS) after TSS is an even rarer event with a described incidence of 0.2% in a single-center TSS series ( 4 ). Less than 40 cases have been described in the literature, two-thirds being preceded by PO subarachnoid hemorrhage (SAH), which might result in delayed cerebral ischemia (DCI) and consequent neurologic deterioration ( 5 , 6 , 7 , 8 , 9 , 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular techniques include coiling, stent protected coiling, covered stents and pipeline devices [ 6 , 9 ] or at least ICA sacrification (coil occlusion). Early diagnosis and treatment of potentially life-threatening complications from ruptured aneurysm, such as subarachnoid hemorrhage, vasospasms or hydrocephalus, have a great impact on the outcome [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%